A divertissement on the financial crisis: We've been speculating - HARNEY, Stefano (Institutional Knowledge at Singapore Management University, 2011)
We’ve been speculating. They say our speculation is going to make things worse. But we keep speculating. We’re on the porch, on the corner, in the bar, at the stove, speculating. We’re with others speculating. We’re in debt, bad debt, with others. We’re speculating on others and they’re speculating on us at the table, round the playground, on the bus. We’ve been speculating, banking on each other. We’ve been counting on others, speculating about them. We’re with them and they’re with us, speculating. Our speculation is scattered. Our speculation is scattered among others. Our speculation is valued among others, others we owe a debt that is not to be paid, a debt we cannot calculate, a debt at a distance, a debt without credit, a debt without end. It’s a queer debt, this debt, a black debt, a debt that plays in us, plays with us. We speculate with this debt, and this debt speculates us. This debt moves us in speculation. Our speculation moves easy. It’s at ease. We don’t work too hard. We work through others, easy. Our speculation comes to us. They say our speculation is idle